TMEM140 is associated with the prognosis of glioma by promoting cell viability and invasion - Li, Bin (J Hematol Oncol, 2015)
BACKGROUND: Gliomas are the most common types of primary brain tumors in the adult central nervous system. TMEM140 is identified as an amplified gene in the human gastric cancer genome. However, the function of TMEM140 in gliomas has not been thoroughly elucidated. The aim of the current study was to determine the clinical significance of TMEM140 expression in patients with gliomas and its effect on tumor cell malignant phenotypes. METHODS: Immunohistochemical analysis and real-time reverse transcription PCR were performed to detect the expression levels of TMEM140 in 70 glioma brain tissue samples. Next, the correlation between the TMEM140 expression levels and the clinical characteristics and outcomes of glioma patients was statistically analyzed. TMEM140 expression was inhibited in two glioma cell lines (i.e., U87 and U373) using a knockdown method with small interfering RNA. Cell Counting Kit-8 and Transwell assays were used to investigate TMEM140 function during cell proliferation, invasion, and migration, respectively. Using flow cytometry and Western blot analysis, we subsequently determined the cell cycle and apoptosis profile of the TMEM140-silenced cells. RESULTS: TMEM140 protein expression was significantly higher in gliomas than in normal brain tissues (p < 0.0001). TMEM140 overexpression was strongly correlated with tumor size, histologic grade, and overall survival time (P < 0.05). TMEM140 decreased cell viability in vitro and dramatically decreased tumor volume in vivo. This phenomenon might be caused by G1 phase cell cycle arrest and cell apoptosis. TMEM140 silencing could suppress the viability, migration, and invasion of glioma cells. CONCLUSIONS: Our results suggest that TMEM140 expression is a prognostic factor that might play an important role in the viability, migration, and invasion of glioma cells. This study highlights the importance of TMEM140 as a novel prognostic marker and as an attractive therapeutic target for gliomas.